Analisis Pengaruh Beban Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan Pada PT. Ital Fran’s Multindo Food Industries Cabang Bali - Sinaga, Intan Krisdayanti; Wiranatha, Agung Suryawan; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2020)
The objective of this research was to study the relationship between workload and working environment on employee performance at PT. Ital Fran’s Multindo Food Industries subdivision Bali. The methods of data collection on this research were  interviews, dissemination of questionnaires and library studies through literature review. Independent variables in this study were the workload (X1) and working environment (X2). Dependent variable was employee performance (Y), and for  intervening variable was employee loyalty (Z). The results showed that workload had no significant effect on employee performance. Meanwhile, the working environment and employee loyalty had positive and significant influences on employee performance. The influence of workload and working environment on employee performance through loyalty was 48% while the remaining 62%   was influenced by other factors or error values. Keywords : Workload, working environment, employee performance, path analysis